Keragaan Pengembangan Kuda Sandelwood di Wilayah Pasola Kabupaten Sumba Barat Daya - Randu, Melkianus D. S.; Hartono, Budi (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
The research objectives were to evaluate farmer characteristics and existing conditions of Sandalwood horse development in Pasola areas at South-West of Sumba Regency. The research was conducted based on a survey method. The research location were Kodi, Kodi Bangedo, and Kodi Balaghar Districts, which were determined by using purposive sampling technique. Data collection were obtained by a depth-interviewing toward 79 respondents of the Sandalwood horse farmers based on the research instrument. The data were analyzed by applying descriptively statistic. The result shows that the farmer characteristics were men in productive age with 21-30 years period of experience in raising the horses, the amount of the horses were under 5, primary school graduated 35,44% and 68,35% have never followed technical training in livestock. The existing conditions of the Sandalwood horse development in the Pasola areas at South-West of Sumba Regency were influenced by some factors such as low capital, traditionally raising management, limitation attention towards the horse products (meat and milk), and low application of technologies in reproduction, feed, and waste aspects.